Levels of trace metals and effect of body size on metal content and concentration in Arctica islandica L. (Mollusca: Bivalvia) from Kiel Bay, Western Baltic - Swaileh, K .M.; Adelung, Dieter (Marine Pollution Bulletin, 1994)
The levels of four trace metals (Cd, Cu, Pb, and Zn) in the whole soft body and in different organs of the ocean quahog Arctica islandica were evaluated from four stations in Kiel Bay, Western Baltic. The relationships between the contents and concentrations of these metals and body size (weight and length) were also investigated. Double logarithmic plots of metal contents and concentrations against dry body weight and shell length, respectively, show straight-line relationships. The results indicate that smaller individuals have higher concentrations of Cu and Zn, two essential metals, while larger individuals have higher concentrations of Cd and Pb, two non-essential metals. The calculated regression slopes of metal content against dry-body weight revealed that Cd and Cu appear to be affected by maturation since two different slopes are observed for both metals before and after maturation. This was not obvious for Pb and Zn. Pooled slopes of metal content against dry-body weight for all animal sizes indicated that Cu and Zn have a one common slope of (0.82) and Cd and Pb another common one of (1.51). Plots of metal concentrations against shell length indicated also that Cu and Zn have one common slope of (−0.54) and Cd and Pb another one of (1.56). Moreover, it was possible to calculate one final slope of (1.53) for Cd and Pb from both content/weight and concentration/length plots. This indicates that A. islandica may have one metabolic strategy for the essential metals and another for the non-essential metals.